Methylophiopogonanone A, an Ophiopogon homoisoflavonoid, alleviates high-fat diet-induced hyperlipidemia: assessment of its potential mechanism - Li, Zhao (Braz J Med Biol Res, 2020)
Methylophiopogonanone A (MO-A), a homoisoflavonoid extracted from Ophiopogon japonicus, has been shown to attenuate myocardial apoptosis and improve cerebral ischemia/reperfusion injury. However, the hypolipidemic effects remain unknown. This study was performed to investigate a potential hypolipidemic effect of MO-A in hyperlipidemia rats, as well as its underlying mechanism of action. A rat model of hyperlipidemia was induced by a high-fat diet (HFD). Animals were randomly divided into three groups (n=8/group): normal control group (NC), HFD group, and HFD+MO-A (10 mg·kg(-1)·d(-1)) treatment group. The effects of MO-A on serum lipids, body weight, activity of lipoprotein metabolism enzyme, and gene expression of lipid metabolism were evaluated in HFD-induced rats. In HFD-induced rats, pretreatment with MO-A decreased the body weight gain and reduced serum and hepatic lipid levels. In addition, pretreatment with MO-A improved the activities of lipoprotein lipase and hepatic lipase in serum and liver, down-regulated mRNA expression of acetyl CoA carboxylase and sterol regulatory element-binding protein 1c, and up-regulated mRNA expression of low-density lipoprotein receptor and peroxisome proliferator-activated receptor α in the liver. Our results indicated that MO-A showed strong ability to ameliorate the hyperlipidemia in HFD-induced rats. MO-A might be a potential candidate for prevention of overweight and dyslipidemia induced by HFD.